Rehabilitation of Former Nickel Mine Soil through Humate and Compost Application for Revegetation Plant Growth Media - Sukriming Sapareng; Erwina Erwina; Taruna Shafa Arzam AR; Annas Boceng; Akmal Akmal; Rosnina Rosnina; Paradillah Ilyas M; Suryanto Suryanto (Postgraduate, University of Mataram, 2025)
Former nickel mine lands often have low soil quality and do not support the growth of revegetation plants. This study aims to evaluate the effect of humic substances and compost on improving the quality of post-nickel mine soil and plant growth media. The experiment was conducted using a completely randomized design in a factorial pattern with three levels of humic and compost treatments, as well as a combination of both, applied to nickel post-mining soil. The results showed that the addition of compost significantly increased the cation exchange capacity (CEC) and availability of nutrients (Ca, Mg, K, Na) in the soil. The addition of humic materials had relatively no significant impact on increasing CEC, but could increase phosphorus levels in the soil. In addition, compost and the combination of compost with humic materials can reduce available heavy metal Cr, although it causes an increase in Ni heavy metal levels in the soil. The results of this study make a significant contribution to the rehabilitation of ex-mining land in a sustainable manner, especially the use of humic materials and compost as a strategy to improve soil quality and increase agricultural productivity. The use of these organic materials is proven to be effective in improving the physical, chemical and biological properties of degraded soils, so it can be a more environmentally friendly approach compared to the use of synthetic chemicals